Coupling of nitrifying granular sludge into microbial fuel cell system for wastewater treatment: System performance, electricity production and microbial community shift. (April 2021) - Zhao, Chuanfu; Wei, Dong; Fan, Dawei; Meng, Shuangyu; Bian, Shuyi; Zhang, Xinwen; Du, Bin; Wei, Qin
Graphical abstract: Highlights: A novel NGS-MFC system was designed for wastewater treatment under batch mode. The COD removal by anode chamber enriched AOB and NGS stability in the cathode. Protein-like substances significantly changed in the two-chambered MFC. Geobacter and Nitrospiraceae were the dominant of the NGS-MFC. Abstract: A novel electrochemical system coupling of nitrifying granular sludge (NGS) into microbial fuel cell (MFC) system was conducted for simultaneous electricity production and wastewater treatment under sequencing batch mode. After 60 days operation, the contaminants of organic and NH4 + -N removal efficiencies of the system were high of 95.43% and 98.55%, respectively. The maximum output voltage and power density of the MFC were average at 170 mV and 33.24 mW/m 2, respectively. According to EEM-PARAFAC model, the soluble microbial products (SMP) released from anode and cathode chambers could be identified two fluorescence components. Additionally, the fluorescence score of protein-like substances changed more obvious than those of humic-like and fulvic acid-like substances. Geobacter and Nitrospiraceae were the dominant functional populations in the anode and cathode chambers, respectively. The result could provide a potential application technology based on NGS-MFC for simultaneously treatment of organic matter and ammonia.